Unravelling the role of AgCr interfacial synergistic effect in Ag/Cr2O3 nanostructured catalyst for the ammoxidation of toluene via low temperature activation of Csp3-H bond - Shankha Shubhra Acharyya; Shilpi Ghosh; Rubina Khatun; Rajaram Bal (Catalysis Communications, 2021)
An environmentally benign and cost-effective synthesis of benzonitrile is reported by direct oxidative cyanation of aromatic Csp3-H bonds of toluene over Ag(I)/Cr2O3 nanostructured catalyst. The catalyst was prepared by a hydrothermal route using cationic surfactant cetyltrimethylammonium bromide and was characterized by powder XRD, XPS, SEM, TEM, TGA, TPD, TPR, UV-visible, FTIR, XANES, and ICP-AES methods. Conjugal effect of Lewis plus Brønsted acidity coupled with AgCr interfacial synergistic interaction appears as detrimental for its high catalytic activity and selectivity (98.4%) for benzonitrile. In situ DRIFTS analysis suggested that the catalytic system proceeded via a reaction pathway explained by Mars-van Krevelen mechanism.